ENTREPRENEUR UNIVERSITY: CHALLENGES AND OPPORTUNITIES - Aimah, Siti (International Conference on Humanity Education and Society (ICHES), 2024)
Abstract The aim of this research is to find an entrepreneurial campus model that can support independence and human resource development and analyze campus opportunities and challenges in the era of society 5.0 in actualizing empowerment assets. Using descriptive research and a qualitative approach as well as a post-positive paradigm, supported by primary and secondary data sources at IAI Darussalam Blokagung, the largest pesantren-based campus in Banyuwangi district which has a business incubator. The data collection technique uses in-depth interviews, participant observation and documentation. The data validity checking technique uses triangulation and data analysis uses three interactive models. The results of the research show that IAI Darussalam Blokagung has a canteen, plantation and livestock business which provides educational operational needs, so that it can be a model for developing Islamic boarding school-based libraries which are required to be independent in developing human resources. Meanwhile, IAI Darussalam Blokagung has proven capable of seizing opportunities in the actualization of entrepreneurial campuses by continuing to innovate in the canteen as one of its business incubators by making bread, mineral water and grass jelly tea consumed daily and event important, showing its success in placing human resources as assets important in developing campus quality